Pathological findings in the pituitary glands of 201 dogs and cats - Polledo, L.; Grinwis, Guy C.M.; Graham, Peter; Dunning, Mark; Baiker, Kerstin (SAGE, 2018)
With the exception of classic functional adenomas in dogs and horses, pituitary lesions are infrequently described in the veterinary literature. Approximately 10% of pituitary glands from asymptomatic humans contain abnormalities but the equivalent proportion in small animals is unknown. Pituitary glands from 136 dogs and 65 cats collected during routine necropsies were examined to determine the prevalence of pituitary lesions and their histopathological diagnosis. Sections were stained with hematoxylin and eosin (HE), periodic acid-Schiff (PAS), Gordon and Sweet's reticulin and immunohistochemistry (against ACTH, GH, MSH-α and prolactin) stains for lesion characterisation.Pituitary abnormalities were identified in 36/136 (26.4%) dogs and 10/65 (15.3%) cats. Cystic changes were the most common lesion in dogs and cats, occurring in 18 (13.2%) dogs and 8 (12.3%) cats. Pituitary neoplasia was detected in 14.1% (12/85) of middle/old aged dogs; 1 (1.5%) cat had pituitary nodular hyperplasia. PAS enabled staining of secretory granules in ACTHimmunoreactive adenomas and reticulin stain helped differentiate them from hyperplastic nodules: adenomas showed PAS positive intracytoplasmic granules and loss of the normal reticulin network. One dog had a pituitary carcinoma with infiltration into the thalamus. Other pituitary abnormalities included: secondary metastases (2 dogs), hypophysitis (4 dogs, 1 cat). In the majority of cases the lesion appeared to be subclinical and could be considered incidental; of those cases with pituitary lesions, clinical manifestations were apparent in 4 dogs (2.9%) and no cats antemortem. Pituitary abnormalities are common in dogs and cats and their wider clinical relevance requires further investigation.